Surgical alternative for treatment of vertical root fracture: A case report - Silva, Emmanuel João Nogueira Leal da; Santos, Gustavo Romão dos; Krebs, Renato Liess; Coutinho-Filho, Tauby de Souza (Iranian Endodontic Journal, 2011)
Vertical root fracture (VRF) has been a great challenge in dentistry; most fractures often result in tooth extraction. Inflammation of tissues around the fractured root is the main reason for tooth extraction. Based on the strategic importance of some fractured teeth, treatment may be necessary and often complicated. However, performing a proper repair or even splinting the fractured segments may result in tooth preservation. Accordingly, in this case we report a new method for fractured tooth preservation. The surgical exposition of the fracture tooth was carried out through the radicular portion of the element via ultrasonic preparation, filling with composed resin and a synthetic hydroxyapatite graft. All these were performed around the tooth which received five sections of low-power laser. The patient was followed for two years with no signs or symptoms of inflammation and gingival recession. In conclusion, the used treatment protocol could be considered as a promising approach for VRF treatment, especially in cases where there is advanced or moderate bone loss in the surrounding sites of the fractured tooth.